Precision and Accuracy Analysis of Forward Method Pipetting and Reverse Method Pipetting by Technology of Medical Laboratory Students Pontianak - Hendra Budi Sungkawa; Reni Endiani (Jurnal Laboratorium Khatulistiwa, 2018)
Abstract: Â Â Pipetting process of using standard pipetting and procedures greatly affect the precision and accuracy of the pipetting which have doneto get the right result and can be trusted then the result being must have lie within the control area and good in precision and accuracy. The purpose of this study is to know the difference of forward method pipetting and reverse method pipetting by Technology of Medical Laboratory Pontianak. The both of methods are have done and then have seen the difference. While the research design which have used in this research is observational analytics with comparative study. Based on the result of the research got result average precision of forward method is 99,25344% and average accuracy value of forwrd method is 96,5983% and average precision of reverse method is 99,65003% and average accuracy value of reverse method is 95,9493%. Of the results values then analyzed with statistic is Wilcoxon test and got result p = 0,000 (p<0,05) then Ha accepted, so there is a difference of forward method pipetting and reverse method pipetting by Technology of Medical Laboratory Pontianak.